Oxovanadium(IV) Complexes with Triazole Based Schiff Base Ligands: Synthesis, Characterization and Antibacterial Study (Journal of Nepal Chemical Society, 2021)
Schiff bases have been synthesized by the reaction of triazole containing primary amine with aromatic carbonyl compounds. The Schiff bases prepared, act as ligand when these are made in contact with oxovanadium (VO2+) ion. Some new mononuclear oxovanadium(IV) complexes have been synthesized by the reaction of Schiff base ligands with vanadyl sulphate (VOSO4.xH2O)  and the complexes are analyzed by different spectroscopic methods; [fourier-transform infrared (FTIR), ultraviolet-visible (UV-Vis.), electron paramagnetic resonance (EPR)], X-ray diffraction (XRD) analysis, elemental analysis, and conductivity measurement. The complexes have been well characterized based on analytical data. The electrolytic nature of the complexes was determined based on the molar conductance values. The powder XRD pattern has been used to determine crystal size and type. The synthesized Schiff base ligands and oxovanadium(IV) complexes were found to be stable in air and moisture at room temperature. On the basis of the physicochemical data, the tentative geometry of the complexes has been proposed. Antibacterial sensitivity of the ligand and its metal complexes have been assayed in vitro against bacterial pathogens viz. growth inhibitory activity of ligands and complexes against pathogens has also been determined.